Social consensus and incomes policy - Durkan, Joe (Economic & Social Studies, 1992)
This paper argues that centralised bargaining as practised in Ireland added to wage inflationary pressure as: the focus of centralised bargaining was the preservation of good industrial relations; the process of wage negotiation was heavily politicised; and, the system evolved into a two-tier bargaining process. Centralised bargaining was not equivalent to an incomes policy framework. It is no surprise that the economy has failed to adjust to the series of internal and external shocks of the past two decades.
Keywords: Social consensus; Incomes policy; Ireland; Centralised bargaining